Determinants of Systemic Risk for Companies Listed on Nepal Stock Exchange (Global Journal of Management and Business Research, 2015)
This paper aims at advancing empirical evidences on financial factors determining systemic risk in the pre-emerging stock market of Nepal as well as to identify whether preemerging stock market and developed and emerging stock markets exposed to the same financial factors that determine systemic risk. A priori hypothesis between relationship of the company-specific financial factors and systemic risk are set based on theoretical framework and previous studies, and tested on the data from 15 listed companies covering a 5-year period, 2009 to 2013. All regular dividend paying and actively traded companies are selected. Based on cross-sectional approach it is revealed that size and profitability are positively associated with the systemic risk, while the dividend payment is negatively related to the risk. The results thus indicate that financial factors have significant predictive power for the systemic risk of a stock investment in Nepal.
Keywords: CAPM; financial factors; listed companies; stock market; systemic risk